THE IMPACT OF ZAKAT ON MONEY DEMAND FUNCTION: EVIDENCE FROM MUZAKKI IN INDONESIA - Masrifah, Atika Rukminastiti; Safitri, Fajrin Intan (Jurnal Ekonomi dan Bisnis Islam (Journal of Islamic Economics and Business), 2021)
Most research in the Islamic economy on the money demand have employed the Keynesian approach, while in this research money demand functions are derived from a microeconomic approach. Thus, the aim of this study is to test and analyze some of the key factors in Islamic money demand model with the microeconomics-based approach, and then, in accordance with Islamic principles, chooses muzakki as the best sample. The data source for this study is 200 muzakki in Java, with a period of 2020. Structural Equation Modelling (SEM) is adopted to examine the relationship between the seven constructs, i.e., zakat, PLS rate, state, regulation, goods and services, conspicuous consumption, and money demand. The systemic relationship between the structures indicates that the integrated model of demand for money has a strong zakat relationship, while reliability and validity have been established. Zakat plays a key role in applying the established paradigm of demand for money in relation to goods and services. Zakat significantly affects both goods and services as well as models of money demand. This proposed new model equation is intended to help each household economic actor increase the demand for philanthropic money. As many muzakki are spread throughout Indonesia, it is expected that the welfare of the poor and the low-income society will gradually improve and, finally, the distribution of income in Indonesia will be on an equal footing.